Recombinant human soluble thrombomodulin attenuates anti-glomerular basement membrane glomerulonephritis in Wistar–Kyoto rats through anti-inflammatory effects. Issue 5 (5th July 2018) - Tachibana, Shohei; Iyoda, Masayuki; Matsumoto, Kei; Wada, Yukihiro; Suzuki, Taihei; Iseri, Ken; Kanazawa, Nobuhiro; Shibata, Takanori
Abstract: Background: Since recombinant human soluble thrombomodulin (RH-TM) has anti-inflammatory properties through neutralizing high-mobility group box 1 protein (HMGB1), the protective effects of RH-TM were examined in anti-glomerular basement membrane (GBM) glomerulonephritis (GN) in Wistar–Kyoto rats. Methods: Rats were injected with nephrotoxic serum (NTS) to induce anti-GBM GN on Day 0, and were given either RH-TM or vehicle from Day 0 to Day 6. Rats were sacrificed 7 days after NTS injection. Results: RH-TM-treated rats had decreased proteinuria and serum creatinine level. RH-TM significantly reduced the percentage of glomeruli with crescentic features and fibrinoid necrosis. In addition, RH-TM-treated rats had significantly reduced glomerular ED1+ macrophage accumulation as well as reduced renal cortical proinflammatory cytokine expression. Furthermore, RH-TM had a potent effect in reducing intercellular adhesion molecule-1 (ICAM-1) expression in kidneys and urine. RH-TM significantly reduced renal cortical mRNA levels for toll-like receptor -2 and -4, known as receptors for HMGB1, and their downstream adopter protein, myeloid differentiation primary respond protein 88 (MyD88). Conclusions: We showed for the first time that anti-inflammatory effects, which were characterized by reduced glomerular macrophage influx concomitant with a marked reduction in proinflammatory cytokines, were involved in the mechanism of attenuating experimental anti-GBM GN by RH-TM. The observed effects might be attributable to the downregulation of ICAM-1 by reducing the HMGB1/TLR/MyD88 signaling pathway.